2013
DOI: 10.1063/1.4802785
|View full text |Cite
|
Sign up to set email alerts
|

Non-Markovianity during the quantum Zeno effect

Abstract: We examine the Zeno and anti-Zeno effects in the context of non-Markovian dynamics in entangled spin-boson systems in contact with noninteracting reservoirs. We identify enhanced non-Markovian signatures in specific two-qubit partitions of a Bell-like initial state, with results showing that the intra-qubit Zeno effect or anti-Zeno effect occurs in conjunction with inter-qubit non-Markovian dynamics for a range of system parameters. The time domain of effective Zeno or anti-Zeno dynamics is about the same orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…In another related study on photosynthetic systems [58], the time domains involved during effective Zeno or anti-Zeno dynamics appeared to be of the same order of magnitude as the non-Markovian time scale of the reservoir correlation dynamics. An earlier study [58] highlighted the subtle links in decay rates due to the Zeno mechanism and information flow between specific partitions of entangled systems.…”
Section: Non-markovianity and Photosynthesismentioning
confidence: 95%
See 1 more Smart Citation
“…In another related study on photosynthetic systems [58], the time domains involved during effective Zeno or anti-Zeno dynamics appeared to be of the same order of magnitude as the non-Markovian time scale of the reservoir correlation dynamics. An earlier study [58] highlighted the subtle links in decay rates due to the Zeno mechanism and information flow between specific partitions of entangled systems.…”
Section: Non-markovianity and Photosynthesismentioning
confidence: 95%
“…An earlier study [58] highlighted the subtle links in decay rates due to the Zeno mechanism and information flow between specific partitions of entangled systems. These findings have implications for a joint Zeno effect-non-Markovian action in the critical tripartite states of the donor-acceptor-sink model of photosynthetic biosystems.…”
Section: Non-markovianity and Photosynthesismentioning
confidence: 98%
“…Since this discovery, both the QZE and QAZE have been studied in many different physical setups such as superconducting qubits 10 23 27 , nanomechanical oscillators 28 , Josephson junctions 29 , disordered spin systems 30 , and localized atomic systems 31 . Generally speaking, the focus has been to study the population decay of quantum systems, whereby the quantum system is prepared in an excited state, and the system is thereafter repeatedly checked to see if the system is still in the excited state or not 24 26 28 29 30 31 32 33 34 35 36 37 . It has then been shown that the decay rate depends on the overlap of the spectral density of the environment and a measurement-induced level width 24 .…”
mentioning
confidence: 99%
“…By a semiclassical analysis they concluded that the QZE is a purely quantum phenomenon without classical analog 34 . Though for a long time, the investigations of QZE and QAZE had mainly focused on the population decay of a quantum system coupled to an environment 3,16,20,3537 , Chaudhry and co-worker switched to also examine the effect of dephasing in their investigation in 2014 38,39 .…”
Section: Introductionmentioning
confidence: 99%